Ethics of genomic newborn screening: a child-centered public health framework - Jungkunz, Martin; Schickhardt, Christoph (Ethik in der Medizin, 2025)
The screening of newborns for severe congenital diseases has been a success story since the 1960s. With the upsurge of genomic sequencing technologies, the question arises: Should genomic Newborn Screening (gNBS) be introduced as general public health measure for all newborns? From an ethical perspective, this leads to the question: What are the relevant moral criteria and points to consider when analyzing and evaluating gNBS as a standard public health procedure in neonatal care?
Gesehen am 28.01.2026